Amerindian Perspectivism and Non-Human Rights - Avelar, Idelber (Revista Ciencia y Cultura, 2013)
This paper starts from Dipesh Chakrabarty’s argument that in the newly named era of the Anthropocene -when human beings have become such a destructive force to the environment that they have acquired the status of geological agents, capable of interfering with the most basic processes of the Earth-, the history of culture can no longer be separated from the history of the species and of nature itself. I then develop the insight that the Anthropocene renews the relevance of Brazilian anthropologist Eduardo Viveiros de Castro’s Ameridian perspectivism, a theory based on the widespread Amerindian postulate of an originary state of indifferentiation between humans and animals, and that the original condition common to humans and animals is not animality, as in Western thought, but humanity itself. The abundance of Amerindian narratives in which animals, plants, and spirits see themselves as humans is analyzed as an Anthropomorphic impulse that paradoxically contains an anti-anthropocentric potential, as "in a world where everything is human, being human is not that special". The contrast between Amerindian anthropomorphism and Western anthropocentrism is further developed in the context of the recent Ecuadorian and Bolivian constitutions, which for the flrst time confer on animals, plants, and bodies of water the condition of juridical subjects endowed with rights. The conclusion points toward the notion of non-human rights as a necessary and urgent task in the era of the Anthropocene.